Synthesis, structural characterisation and theoretical studies of a novel pyridazine derivative: Investigations of anti-inflammatory activity and inhibition of α-glucosidase - Zaoui, Younes; Ramli, Youssef; Tan, Sang Loon *; Tiekink, Edward R. T. *; Chemlal, L.; Mague, Joel T.; Taoufik, Jamal; Faouzi, M. E. A.; Ansar, M'hammed (Elsevier, 2021)
X-ray crystallography on pyridazine 1 (ethyl 2-(3-methyl-4-(4-methylbenzyl)-6-oxopyridazin1(6H)-yl)acetate) shows the planar pyridazinyl ring to exhibit significant delocalisation of πelectron density over the constituent atoms and to be substituted with oxo, methyl, (4- methylphenyl)methyl and N-bound ethylacetate groups. While three of the ring-bound atoms are close to co-planar with the ring, the ethylacetate group is not; the latter exhibits a definitive kink in its conformation. In the molecular packing of 1, helical supramolecular chains along the b-axis are formed through O- and N-methylene-C–H…O(carbonyl) and Omethylene-C–H…π(pyridazinyl) interactions. The chains are connected into a supramolecular layer by π(pyridazinyl)…π(phenyl) interactions. The flat layers stacks along the c-axis 2 without directional interactions between them. The geometry-optimisation of 1 resulted in the straightening of terminal ethylacetate group but no other substantial changes. Computational chemistry shows the most stabilising interactions in the crystal are due to the π(pyridazinyl)…π(phenyl) (-10.7 kcal/mol) followed by O- and N-methylene-C–H…O(carbonyl) (-9.5 and -9.0 kcal/mol, respectively). The most prominent identified interlayer interaction is a weak methylene-C–H···N(pyridazinyl) contact. Throughout, comparisons are made with the phenyl analogue of 1, namely 2. Most notably, the lattice energy of 1 is approximately 4.1 kcal/mol more stable than that of 2, an observation related to the influence upon the molecular packing exerted by the methyl substituent of 1. Compound 1 exhibits moderate inhibition against α-glucosidase, compared to Acarbose, and weak heatinduced haemolysis inhibition.